2D material broadband photodetectors. Issue 2 (17th December 2019) - Yao, Jiandong; Yang, Guowei
Abstract : 2D materials and their hybrid structures have high application prospects in broadband photodetection, making them promising complements to traditional schemes. Abstract : Our review provides a comprehensive overview of the latest evolution of broadband photodetectors (BBPDs) based on 2D materials (2DMs). We begin with BBPDs built on various 2DM channels, including narrow-bandgap 2DMs, 2D topological semimetals, 2D charge density wave compounds, and 2D heterojunctions. Then, we introduce defect-engineered 2DM BBPDs, including vacancy engineering, heteroatom incorporation, and interfacial engineering. Subsequently, we summarize 2DM based mixed-dimensional (0D–2D, 1D–2D, 2D–3D, and 0D–2D–3D) BBPDs. Finally, we provide several viewpoints for the future development of this burgeoning field.